2019
DOI: 10.1016/j.biochi.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of miRNAs in esophageal cancer contributes to radioresistance and limits efficacy of therapy

Abstract: The five-year survival rate of esophageal cancer patients is less than 20%. This may be due to increased resistance (acquired or intrinsic) of tumor cells to chemo/radiotherapies, often caused by aberrant cell cycle, deregulated apoptosis, increases in growth factor signaling pathways, and/or changes in the proteome network. In addition, deregulation in non-coding RNA-mediated signaling pathways may contribute to resistance to therapies. At the molecular level, these resistance factors have now been linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 89 publications
0
33
0
Order By: Relevance
“…Through regulating gene expression, miRNAs regulate a variety of important biological functions, such as proliferation, apoptosis, differentiation, migration, invasion and drug resistance. Genetic or epigenetic changes in cancer cells can induce abnormal expression of miRNAs, thus causing abnormal expression of their target genes [16][17][18][19][20][21]. miRNAs function through 6-7 base complementary binding to target mRNA and inhibition of target gene expression at the level of protein [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Through regulating gene expression, miRNAs regulate a variety of important biological functions, such as proliferation, apoptosis, differentiation, migration, invasion and drug resistance. Genetic or epigenetic changes in cancer cells can induce abnormal expression of miRNAs, thus causing abnormal expression of their target genes [16][17][18][19][20][21]. miRNAs function through 6-7 base complementary binding to target mRNA and inhibition of target gene expression at the level of protein [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the association between microRNAs (miRs) and cancer has been investigated. Recent studies have demonstrated that abnormal expression of miRs is detected in the serum of patients with ESCC (3)(4)(5). These findings may provide new direction for further study of the progression of ESCC and to determine novel potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 82%
“…Furthermore, siRNA-mediated knockdown of FAM201A exhibited decreased proliferation in ESCC cell lines Eca109 and Eca109R. However, when Eca109R cells transfected with FAM201A mimics, the authors did not observe any increased proliferation because the expression level of FAM201A was already at a higher level in Eca109R cells [ 10 ]. Moreover the knockdown of FAM201A in a xenograft tumor mouse model significantly blocked tumor growth with decreased tumor volume and weight, indicating that FAM201A could induce radiosensitivity both in vitro and in vivo in the model system [ 13 ].…”
Section: Detailed Regulation Of Radiosensitivity In Escc Through Lmentioning
confidence: 99%
“…Several studies have demonstrated the association of non-coding RNAs in regulating various cancer hallmarks, including the radioresistance processes in cells [ 8 , 9 ]. Our previous study suggested several microRNAs (miRNAs) dictating sensitivity and resistance against radiotherapy EC patients [ 10 ]. Furthermore, recent studies have reported the association of long non-coding RNAs (lncRNAs) with altered patients’ responses towards radiation therapy due to their active involvement in DNA damage response (DDR), apoptosis, and cell cycle arrest [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%